Bounds on the tau and muon neutrino vector and axial vector charge radius (2003)
ABSTRACT: Experimental evidence for neutrino oscillations implies that neutrinos are the first elementary particles whose properties cannot be fully described within the standard model. This hints at the possibility that other properties of these intriguing particles might substantially deviate from the predictions of the SM, and is presently motivating vigorous efforts, on both theoretical and experimental sides, to understand in more depth the detailed properties of neutrinos and of their interactions. In particular, the electromagnetic properties of the neutrinos can play important roles in a wide variety of domains such as cosmology and astrophysics and can also provide a viable explanation for the observed depletion of the electron neutrino flux from the Sun. The electromagnetic interaction of Dirac neutrinos is described in terms of four form factors. The matrix element of the electromagnetic current between an initial neutrino state in with momentum pi and a final state with momentum reads.